Tinjauan Persaingan Usaha Dagang Antar Warung Kopi Tradisonal Dan Warung Kopi Modern Berdasarkan Undang Undang Nomor 5 Tahun 1999: (Studi Kasus, Warung Kopi Kape Kota Gorontalo) - Mohamad Siddeq Husein Ischak; Mutia Ch Thalib; Julius T. Mandjo (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
This study aims to determine the causes of trade competition between traditional and modern coffee shops in the city of Gorontalo and to understand the forms of business competition between traditional and modern coffee shops in terms of Law No. 5 of 1999, based on the title raised in this study, researchers see whether business actors have implemented the law mentioned above. This study uses empirical methods. The data collection process examined by researchers in this study were primary data and secondary data. Data collection techniques that support and relate to this research are direct interviews, observation, documentation and literature study. The results of this study indicate that there are 2 (two) things that need attention, namely first, in the perspective of existing competition, the findings found by the author are more focused on the balanced form of coffee provided from the two types of Warkop in the realm of research, from various types The coffee that several Warkop are trying to offer actually has a tendency for collectors to try to manipulate the market, and in the future this will be seen as a form of unhealthy competition. Second, the form of monopoly that arises in business competition in the realm of research, is the reason for the author to investigate further in applying law number 5 of 1999 concerning the prohibition of monopolistic practices and unfair business competition. If we look at article 13 regarding oligopsony and how business actors apply this law, it is clear that there is a geographical indication that is used by individuals to control the coffee because before the coffee is widely distributed, it must be recorded and directly purchased at a low price by these persons.